Pertanggungjawaban Pidana Pelaku Tindak Pidana Korupsi dalam Implementasi Program Internet Desa di Kabupaten Flores Timur - Maria Krismastina Benga Kopon; Debi F. Ng Fallo; Sigit P. Sonbait (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2025)
This study aims to analyze the form of criminal liability imposed on perpetrators of corruption involving internet village funds in Flores Timur Regency. Corruption in the management of village funds, particularly those allocated for internet infrastructure development, has become a serious concern due to its direct impact on the quality of public services and the welfare of rural communities. This research employs a normative juridical method with a case approach and the analysis of relevant statutory regulations. Data were obtained through literature study and case documentation. The findings indicate that perpetrators of corruption in the internet village fund program can be held criminally liable under Law Number 31 of 1999 in conjunction with Law Number 20 of 2001 concerning the Eradication of Corruption. Criminal liability involves elements of fault, unlawful acts, and state financial losses. In addition, the role of law enforcement agencies and public oversight are crucial factors in the enforcement of laws against such criminal acts.